Predictors of Serum 25-Hydroxyvitamin D Concentrations among a Sample of Egyptian Schoolchildren - Mones M. Abu Shady; Mai M. Youssef; Ebtissam M. Salah El-Din; Ola M. Abdel Samie; Hala S. Megahed; Samar M. E. Salem; Manal A. Mohsen; Ali Abdel Aziz; Safinaz El-Toukhy (The Scientific World Journal)
Objective. To assess the level of 25-hydroxyvitamin D status among a sample of Egyptian schoolchildren and to evaluate predictors of deficiency and insufficiency. Subjects and Methods. A cross-sectional study comprising 200 prepubescent schoolchildren aged from 9 to 11 years was performed. A questionnaire including frequency of midday sun exposure, milk intake, physical activity, and level of maternal education was taken. Body mass index (BMI) was calculated; serum 25-hydroxyvitamin D [25(OH)D], serum calcium, phosphorus, and parathyroid hormone were measured. Results. Vitamin D deficiency [serum 25(OH)D < 20 ng/mL] was detected in 11.5% of subjects while its insufficiency (serum 25(OH)D is between 20 and 29.9 ng/mL) was detected in 15%. Results revealed that obesity, low physical activity, low sun exposure, and low maternal education level are significant predictors of insufficiency, though female gender, low maternal education level, and low milk intake are significant predictors of deficiency. Lower serum phosphorus and higher serum parathyroid hormone were significantly associated with both deficiency and insufficiency (p<0.05). Conclusion. Vitamin D deficiency and insufficiency are common among schoolchildren in Egypt. Food fortification, vitamin D supplementation, and increasing maternal awareness about the importance of physical activity and exposure of their children to ultraviolet light may help to overcome this problem.